Urban traffic controller and simulation platform design - Zhu, Siyou (2018)
This master thesis tries to put urban traffic signal control into a scheduling framework, in which all parameters of a traffic network, e.g. volumes of each link, flows between links, states of traffic lights, etc., are translated into a novel model. With a goal to minimize the total delay time in the whole network through control process, an integer linear programming problem is set up so that some tools like CPLEX can be applied to find the best solution to the problem. Besides, this master thesis studies the way to build an integrated model participated with both vehicles and pedestrians and set up an urban traffic network to evaluate traffic network components, which includes both pedestrians and vehicles via PTV Vissim, a traffic microscopic multi-modal traffic simulation software.